The Impact of Ecotourism on the Surrounding Community’s Economy and Social Life - Apriliani, Anggie Noer; Farimah, Siti; Wilis, Ratna (LifeSciFi, 2025)
The rapid development of Asia Farm Ecotourism as an educational tourism destination significantly contributes to the stimulation of the local economy and social life. The aim of this research is to analyze the economic and social impacts generated by Asia Farm on the communities. The study employs a qualitative descriptive approach through field observations, in-depth interviews, and a literature review from various relevant sources. The results indicate that Asia Farm significantly contributes to improving community welfare through the creation of local employment, growth of culinary SMEs, and the emergence of supporting tourism businesses such as bicycle rentals and educational mini-cinemas. Socially, the destination fosters community awareness of environmental cleanliness, strengthens social interactions, and cultivates a service-oriented culture that is welcoming to tourists. The findings also reveal a mutually reinforcing relationship between economic and social aspects, where increased community income positively affects social stability and vice versa. The implications of this study highlight that sustainable ecotourism, such as Asia Farm, can serve as a model for community-based economic development oriented toward welfare, sustainability, and social harmony in modern urban areas.